LASER AS A VISUALIZATION DEVICE - Singh, Risham; Singh, Gurpreet; Grabusts, Peteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
As known to the prior characteristics of the laser, the new advanced technologies are based on the lasers. It can be used in different ways like scanning, displaying, engraving, cutting, drilling, marking, and many more. In this article, a discussion is made about the use of lasers as a device of visualization in climatic conditions like snow, fog and heavy rain. The existing technology “LiDAR” is one of the systems that will be discussed. LiDAR is a Light Detection and Ranging device used for driving the autonomous vehicles and are also installed on aircrafts in order to scan a vast area like forest, cities, etc. Lidar has been contributing a lot to our intelligence of the Earth’s atmosphere for the past few years [2]. But with so many features, this system has its own limitations, with some conditions such as in bad weather and unable to recognize the white color. In this research two types of red-lasers are being used i.e. Diode and He-Ne Laser, of wavelength 650nm & 632.8 nm respectively. Also a green diode laser of wavelength 532nm is used. With the help of these lasers, we will be able to conclude if the laser is able to reflect back from water, snow and fog or it will pass through them without detecting. With this, we can also justify the loss of power that laser generates.